Experimental investigation of the micro-hardness of EN-31 die steel in a powder-mixed near-dry electric discharge machining method - Sundriyal, Sanjay (Strojniški vestnik, 2020)
The Powder-Mixed Near-Dry Electric Discharge Machining (PMND-EDM) methodology has proven to be efficient in terms of machining rate, surface morphology, and environmental friendliness, unlike traditional EDM. In this study, the presence of a conductive metallic powder (zinc) in the dielectric medium was responsible for changing the topography of the workpiece (EN-31) and resulted in a higher micro-hardness value of the machined component. In this research, an approach has been made to optimize the significant process parameters by using a Taguchi L9 orthogonal array (OA) to obtain machined components with higher values of micro-hardness, which was measured in terms of Vickers hardness HV. The selected process parameters were tool diameter, mist flow rate, metallic powder concentration, and dielectric mist pressure. By introducing foreign particles (metallic powder), the topography of the machined products has been improved, and the micro-hardness value was found to be enhanced. The confirmation experiment was performed for optimal process parameter settings, and the enhanced microhardness value was found to be 506.63 HV in the machined EN-31 die steel.
Keywords: electric discharge machining; elektroerozijska obdelava; micro-hardness; mikrotrdota; optimizacija; optimization; powder; prah